Survey of ICT and Education in Africa : Liberia Country Report - Mangesi, Kofi (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Liberia is in the process of developing a comprehensive ICT policy called E-Liberia: vision 2010, yet efforts at increasing access and use of ICTs have already begun under the telecommunication policy. In the education sector, Liberia has no specific policy on ICTs, but there is wide acknowledgement that ICTs need to be incorporated in schools and universities.